ZAKAT DALAM PERSPEKTIF MAQASHID AL-SYARIAH - Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2015)
Zakat as one of the pillars in Islam provides a alternative of social protection. Paying for zakat is not only a manifestation of worshipping Allah but also a social action to support for the improvement of people’s life quality. Zakat is not a goal but it is a means to achieve social justice and a means to reduce the number of poverty as well. Therefore, good management of zakat under the principles of syariah is a must. Kata kunci: Zakat, Pengeloaan Zakat, Maqashid al-Syariah